Functional Roles of p38 Mitogen-Activated Protein Kinase in Macrophage-Mediated Inflammatory Responses - Yanyan Yang; Seung Cheol Kim; Tao Yu; Young-Su Yi; Man Hee Rhee; Gi-Ho Sung; Byong Chul Yoo; Jae Youl Cho (Mediators of Inflammation)
Inflammation is a natural host defensive process that is largely regulated by macrophages during the innate immune response. Mitogen-activated protein kinases (MAPKs) are proline-directed serine and threonine protein kinases that regulate many physiological and pathophysiological cell responses. p38 MAPKs are key MAPKs involved in the production of inflammatory mediators, including tumor necrosis factor-α (TNF-α) and cyclooxygenase-2 (COX-2). p38 MAPK signaling plays an essential role in regulating cellular processes, especially inflammation. In this paper, we summarize the characteristics of p38 signaling in macrophage-mediated inflammation. In addition, we discuss the potential of using inhibitors targeting p38 expression in macrophages to treat inflammatory diseases.